THE IMPACT OF INEQUALITY AND EXCLUSION IN NICARAGUA’S POLITICAL CONFLICT FROM ITS INDEPENDENCE UNTIL THE BEGINNING OF THE 20TH CENTURY - Abelardo Baldizón, José (2019)
In Nicaragua, from the Independence until the beginning of the 20th century, the political conflict was marked by violence. This resulted from the inability of the warring factions to accept the right of the adversary of becoming the country’s government. This plunged the country into a dynamic of mutual exclusion and constant civil wars. The key factors in generating this dynamic were: social stratification, political clientelism, and personalism. All of them produced an unequal and excluding access to the political system. Social stratification was based on a hierarchical conception of the social order that caused a deep inequality in the distribution of wealth and the ability to participate in politics. In the Nicaraguan political system, this inequality was reproduced in the form of hierarchical client networks that struggle against each other to control the State. At the same time, those closest to the top of the hierarchy had greater possibilities to influence the political decision-making process. As a result, inclusion/exclusion in the political system was regulated, first, by the position in the social and political hierarchy a person had and, second, by the closeness of his ties with the members of the political camp that controlled the state apparatus.